Fundamentals of plant breeding and hybrid seed production - Agrawal, Rattan Lal (Science publishers, Inc., 1998)
This text explores the fundamentals of plant breeding and hybrid seed production. It examines issues including male sterility, composite and synthetic varieties and disease resistance breeding.